Quality of Supervised Research Report in Relation to Postgraduate Medical Qualifications of Bangladesh (Bangladesh Journal of Medical Education, 2014)
In any academic field the question of quality is central issue. Evaluation of the quality in supervised research in medical education is very important in higher education and teaching. The purpose of the supervised research project is to provide the learner an experience in scientific writing, to familiarize the student with the steps of research, to promote critical and analytical thinking of the learner and to contribute something new to knowledge base. The objectives of this study were to determine the quality in postgraduate supervised research report writing, according to the standard recommended and implied by the post graduate medical institutes of Bangladesh and thus to assess the achievement of the intended purposes. For that an exploratory and descriptive study was performed on 64 theses and dissertations submitted during the period of 2008-2010 in two selected post graduate medical institutes of Dhaka city. The overall quality was found marginal in 93.8% (60) of the reports. There were indications that the prescribed standard was not followed properly. It was observed from the study that there are problems in learning and inadequacy in fulfillment of the purpose of supervised research program. It was perceived that probably the supervision was not enough. Theoretical knowledge gap was also apparent at various levels. To address these issues planning, designing, supervision and assessment systems of supervised research program in relation to the postgraduate medical qualifications of Bangladesh needs critical attention.DOI: http://dx.doi.org/10.3329/bjme.v3i1.18588 Bangladesh Journal of Medical Education Vol.3(1) 2012: 1-7